2017
DOI: 10.1139/cjpp-2016-0498
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and theanine exert opposite effects on attention under emotional arousal

Abstract: Tea is perceived as more relaxing than coffee, even though both contain caffeine. L-theanine in tea may account for the difference. Consumed together, caffeine and theanine exert similar cognitive effects to that of caffeine alone, but exert opposite effects on arousal, in that caffeine accentuates and theanine mitigates physiological and felt stress responses. We evaluated whether caffeine and theanine influenced cognition under emotional arousal. Using a double-blind, repeatedmeasures design, 36 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…Caffeine can accentuate global processing of visual attention on the hierarchical shape task and improve rapid visual information processing accuracy. 42,43 Besides, acetylsalicylic acid decreased latency and reaction time of visually evoked event-related potentials, possibly via the serotonergic transmitter system. 44 NSAIDs showed neuroprotective and memory enhancing effect against chlorpromazine induced Parkinson’s model.…”
Section: Discussionmentioning
confidence: 94%
“…Caffeine can accentuate global processing of visual attention on the hierarchical shape task and improve rapid visual information processing accuracy. 42,43 Besides, acetylsalicylic acid decreased latency and reaction time of visually evoked event-related potentials, possibly via the serotonergic transmitter system. 44 NSAIDs showed neuroprotective and memory enhancing effect against chlorpromazine induced Parkinson’s model.…”
Section: Discussionmentioning
confidence: 94%
“…Since theanine and Arg reduce stress and caffeine and EGCG antagonizes the action of theanine [ 16 , 17 ], we examined how these levels affect adrenal hypertrophy in stressed mice. In mice, adrenal hypertrophy was suppressed when the amount of theanine ingested was 0.32 mg/kg or more.…”
Section: Discussionmentioning
confidence: 99%
“…Theanine exhibits an excellent stress-reducing effect on mice and humans [ 12 , 13 ]. However, the effect of theanine is antagonized by caffeine and epigallocatechin gallate (EGCG), which are two major components of green tea [ 14 , 15 , 16 ]. In contrast, the stress-reducing effect of theanine is enhanced by arginine (Arg), which is the second most abundant amino acid in Japanese green tea [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that differences in the quantities and ratios of matcha components affect the efficiency of its stress-reducing action. While caffeine and epigallocatechin gallate (EGCG) antagonize the stress-reducing effect of theanine [12, 13, 14], arginine (Arg), the second most abundant amino acid in Japanese green tea, enhances the effect of theanine [13]. When tea leaves are protected from direct sunlight, theanine levels remains high because it is broken down to glutamate and ethylamine when exposed to sunlight, and the former is used for the biosynthesis of EGCG [15, 16].…”
Section: Introductionmentioning
confidence: 99%